Development of Integrated Student Worksheets Stacking Multiplication Tricks Class III Elementary Students - Sari, Milda (Institut Agama Islam Negeri Palopo, 2021)
Article research on the development of the right trick LKS was made to determine the prototype of the development of the LKS, to find out the validity of the development of the right trick LKS in stacking multiplication material, and to measure the effectiveness of the stacking multiplication skill worksheet in grade III students at SDN 50 Bulu Datu Palopo. This research method is the method of research & development (R&D). The development model used in this development is the four. D model, but this study only performs the 3D stages, namely define, design, develop. The subjects in this study were class III.B SDN Bulu Datu Palopo totaling 24 students. The data collection techniques in this study used observation, tests, documentation, interviews, and questionnaires. Based on the needs analysis shows that in learning mathematics multiplication stacking requires a teaching material in the form of stacked multiplication worksheets. Data analysis techniques to test the effectiveness using the T-test and to test the validity using Aiken's formula. The results of this study indicate that the development of the stacking multiplication trick worksheet developed was declared valid by the three validators with a recapitulation of the value of 0.67. The precise trick LKS teaching materials are categorized as effective based on the results of the T-test and the pre-test and post-test results.